Are phonological processing deficits part of the broad autism phenotype? - Bishop, D; Maybery, M; Wong, D; Maley, A; Hill, W; Hallmayer, J (2004)
Two tests of phonological processing, nonword repetition, and nonsense passage reading, were administered to 80 probands with autistic disorder or PDDNOS (index cases) and 59 typically developing controls, together with their parents and siblings. In addition, parents completed a questionnaire about history of language and literacy problems, and all participants were given tests of verbal (VIQ) and performance IQ (PIQ). Parents also completed the Autism-Spectrum Quotient, which was used to index the broad autism phenotype. Index probands scored well below control probands on the two phonological tests. However, on neither phonological measure did index relatives differ from control relatives. Within the index group, there was no relationship between the proband's level of VIQ, or age at achieving phrase speech, and phonological score of relatives. VIQ was the only measure to show any familiality within the index group. Reported history of language and literacy problems did not differentiate index parents from control parents overall, but those who were categorized as cases of the broad phenotype reported more history of language and literacy problems than did other index parents. However, they did not have poorer scores on the phonological measures. It is concluded that phonological processing deficits are not part of the broad autism phenotype.